Pengaruh Rekrutmen dan Seleksi pada Kompensasi Langsung dan Kinerja Karyawan di Industri Tekstil - Sundjoto, Sundjoto (Universitas Prasetiya Mulya, 2024)
To face an increasingly stringent environment and also try to gain influence from the free market in Indonesia, the textile industry must prepare its human resources and expect them to emerge from conditions of tight competition, especially from the work ability or performance utilized to support company activities and provide added value on the products produced. This research is aimed at finding out the effect of selection and recruitment on employee compensation and performance where the data collection testing technique was carried out using Structural Equation Modeling using AMOS V.4.01. This research was conducted at several textile companies in the East Java region. The number of respondents taken for this research was 120 people from all of the textile company employees who were the research subjects. The scientific findings of this research show that all variables are estimated to have a significant influence on employee performance and show that employee performance cannot be achieved optimally without determining compensation first.